In situ response of the linuron degradation potential to linuron application in an agricultural field. Issue 3 (13th May 2013) - Bers, Karolien; De Mot, René; Springael, Dirk
Abstract: To assess the involvement of the genus Variovorax and the linuron hydrolase gene libA in in situ linuron degradation in agricultural fields, changes in Variovorax community size and composition, in libA abundance and in linuron mineralization capacity were monitored in field soil plots either treated or not with a linuron‐containing herbicide mixture. Changes in Variovorax community composition, due to the proliferation of a hereto unknown Variovorax phylotype D, and increases in libA numbers occurred concomitant to increases in linuron mineralization capacity in the plot treated with the herbicide mixture. The observations suggest that Variovorax and libA proliferated as a response to linuron and hence their contribution to in situ linuron degradation. The involvement of Variovorax phylotype D and libA in linuron degradation in the examined soil was supported by laboratory soil microcosm experiments. Attempts to enrich in suspended cultures and isolate the organism corresponding to phylotype D from the soil were unsuccessful as the enrichment resulted in replacement of Variovorax phylotype D by other Variovorax phylotypes. This illustrates that linuron‐degrading strains isolated by liquid enrichment cultures are not always representatives of those responsive to linuron in the field, although the genus specificity of linuron degradation was retained.